Constraints on Argument Linearization in German. Issue 1 (12th January 2018) - Ellsiepen, Emilia; Bader, Markus
Abstract : In this article we present experimental findings on the acceptability of different argument orders in the German middle field. Our study pursues two goals: First, to evaluate a number of surface constraints on German argument order that have been proposed in the literature, and second, to shed new light on how gradient constraints jointly determine sentence acceptability. In four experiments, we investigated the impact of surface constraints relating to animacy, thematic roles, definiteness and case. While we are able to confirm an influence of most constraints under investigation, the resulting constraint hierarchy does not coincide with any hierarchy put forward so far in the literature, to the best of our knowledge. With regard to gradience, our results can be accounted for either by an OT variant incorporating a notion of markedness, or by a fully quantified model using constraint weights. For the latter, however, we provide evidence against uniform penalties associated with constraint violations.